The Future of Reef Ecosystems in the Gulf of Mexico: Insights From Coupled Climate Model Simulations and Ancient Hot-House Reefs - Dee, Sylvia G.; Torres, Mark A.; Martindale, Rowan C.; Weiss, Anna; DeLong, Kristine L. (Frontiers in Marine Science, 2019)
Shallow water coral reefs and deep sea coral communities are sensitive to current and future environmental stresses, such as changes in sea surface temperatures (SST), salinity, carbonate chemistry, and acidity. Over the last half-century, some reef communities have been disappearing at an alarming pace. This study focuses on the Gulf of Mexico, where the majority of shallow coral reefs are reported to be in poor or fair condition. We analyze the RCP8.5 ensemble of the Community Earth System Model v1.2 to identify monthly-to-decadal trends in mean Gulf of Mexico SST. Secondly, we examine projected changes in ocean pH, carbonate saturation state, and salinity in the same coupled model simulations. We find that the joint impacts of predicted higher temperatures and changes in ocean acidification will severely degrade Gulf of Mexico reef systems by the end of the 21st century. SSTs are likely to warm by 2.5 to 3C; while corals do show signs of an ability to evolve toward higher temperatures, current coral species and reef systems are likely to suffer major bleaching events in coming years. We contextualize future changes with ancient reefs from paleoclimate analogues, periods of Earth's past that were also exceptionally warm, specifically rapid ``hyperthermal" events. Ancient analogue events are often associated with extinctions, reef collapse, and significant ecological changes, yet reef communities managed to survive these events on evolutionary timescales. Finally, we review research which discusses the adaptive potential of the Gulf of Mexico's coral reefs, meccas of biodiversity and oceanic health. We assert that the only guaranteed solution for long-term conservation and recovery is substantial, rapid reduction of anthropogenic greenhouse gas emissions.